Evaluation of some additives for acceptability with zinc phosphide bait against rodent (Bangladesh Journal of Agricultural Research, 2016)
Laboratory and field study were conducted to evaluate the effects of some bait additives namely molasses, sugar, dry fish and powder milk mixed with wheat flour to increase the acceptability of additives mixed bait and the efficiency of poison bait. The findings showed that the additives mixed plain bait led to an increase the palatability and consumption rate. The most accepted plain bait for rodent was the bait combination molasses + wheat flour followed by sugar + wheat flour. The highest mortality was observed from the bait in the treatment combination powder milk + dry fish + wheat flour +Zn3P2 (90%) followed by (powder milk + molasses + dry fish + wheat flour + Zn3P2) (80%) in laboratory. The average zinc phosphide bait consumption was highest in the treatment dry fish + wheat flour +Zn3P2 (1.56 g/rat/day) followed by molasses + dry fish + powder milk + wheat flour + Zn3P2 (0.80 g/rat/day). All these additives mixed with zinc phosphide increase the consumption rate and the efficacy of bait. In field trial the higher population reduction (76-86%) was achieved from the bait dry fish + wheat flour + Zn3P2 followed by dry fish + powder milk + wheat flour + Zn3P2 (76-80%) and the lowest in powder milk + wheat flour + Zn3P2 (30%). All these additives mixed with zinc phosphide increased the consumption rate and the efficacy of poison bait.Bangladesh J. Agril. Res. 41(3): 471-480, September 2016